(untitled) (Journal of Social Sciences Review, 2023)
From many decades the currency of Pakistan has many flew and fawn, in this universe every one need money for their sustain so the thing is that people not knew that how to utilize their resources to make more and more and get more and more, here we try to focus on the word money that how to utilize it in a precious and sustainable way to make preductule outcomes so let’s begin the word stock exchange! Everyone hair about this word but there are few connections with it to generate money in a bulk form. Generally the people of industrious, shareholders and many companies are involved in it like as PSO, Unilever, Engro, FFC, OGDC, KAPCO, HUBC, AKBL, TRG etc. where the other rest of people are? are they not know the markets trends that how to make bid and ask and through what they can make their risk minimize as a term of money investment so here we took the topic which is totally related with the utilizing the term money and make money because everyone want this and most of are getting this but rest of having no knowledge how to make it.